High‐Affinity "Click" RGD Peptidomimetics as Radiolabeled Probes for Imaging αvβ3 Integrin. (3rd July 2017) - Piras, Monica; Testa, Andrea; Fleming, Ian N.; Dall'Angelo, Sergio; Andriu, Alexandra; Menta, Sergio; Mori, Mattia; Brown, Gavin D.; Forster, Duncan; Williams, Kaye J.; Zanda, Matteo
Abstract: Nonpeptidic Arg‐Gly‐Asp (RGD)‐mimic ligands were designed and synthesized by click chemistry between an arginine–azide mimic and an aspartic acid–alkyne mimic. Some of these molecules combine excellent in vitro properties (high αv β3 affinity, selectivity, drug‐like log D, high metabolic stability) with a variety of radiolabeling options (e.g., tritium and fluorine‐18, plus compatibility with radio‐iodination), not requiring the use of chelators or prosthetic groups. The binding mode of the resulting triazole RGD mimics to αv β3 or αIIb β3 receptors was investigated by molecular modeling simulations. Lead compound12 was successfully radiofluorinated and used for in vivo positron emission tomography/computed tomography (PET/CT) studies in U87 tumor models, which showed only modest tumor uptake and retention, owing to rapid excretion. These results demonstrate that the novel click RGD mimics are excellent radiolabeled probes for in vitro and cell‐based studies on αv β3 integrin, whereas further optimization of their pharmacokinetic and dynamic profiles is necessary for successful use in in vivo imaging. Abstract : Small‐molecule "click" RGD ligands were found to display excellent in vitro properties and offer a variety of radiolabeling options (including 18 F). The binding mode to αv β3 or αIIb β3 receptors was studied by molecular modeling. Radiofluorination and PET/CT studies on compound12 in tumor models showed that these mimics are excellent radiolabeled probes for in vitro and cell‐based studies on αv β3 integrin, but further pharmacokinetic and dynamic profiling is required for in vivo imaging.